An incentive mechanism for data sharing based on blockchain with smart contracts. (May 2020) - Xuan, Shichang; Zheng, Li; Chung, Ilyong; Wang, Wei; Man, Dapeng; Du, Xiaojiang; Yang, Wu; Guizani, Mohsen
Abstract: Data sharing techniques have progressively drawn increasing attention as a means of significantly reducing repetitive work. However, in the process of data sharing, the challenges regarding formation of mutual-trust relationships and increasing the level of user participation are yet to be solved. The existing solution is to use a third party as a trust organization for data sharing, but there is no dynamic incentive mechanism for data sharing with a large number of users. Blockchain 2.0 with smart contract has the natural advantage of being able to enable trust and automated transactions between a large number of users. This paper proposes a data sharing incentive model based on evolutionary game theory using blockchain with smart contract. The smart contract mechanism can dynamically control the excitation parameters and continuously encourages users to participate in data sharing.